NAADP-induced calcium release in sea urchin eggs. - Galione, A; Patel, S; Churchill, G (2000)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is the most potent activator of Ca2+ release from intracellular stores described. It acts on a mechanism distinct from inositol trisphosphate and ryanodine receptors, the two major Ca2+ release channels characterised. NAADP-gated Ca2+ release channels do not appear to be regulated by Ca2+ and may be better suited for triggering Ca2+ signals rather than propagating them. They exhibit a remarkable pharmacology for a putative intracellular Ca2+ release channel in that they are selectively blocked by potassium and L-type Ca2+ channel antagonists. Furthermore, in contrast to microsomal Ca2+ stores expressing IP3Rs and RyRs, those sensitive to NAADP are thapsigargin-insensitive, suggesting that they may be expressed on a different part of the endoplasmic reticulum. Perhaps the most unusual feature of the NAADP-gated Ca2+ release mechanisms is its inactivation properties. Unlike the mechanisms regulated by IP3 and cADPR in sea urchin eggs which after induction of Ca2+ release appear to become refractory to subsequent activation, very low concentrations of NAADP are able to inactivate NAADP-induced Ca2+ release fully at concentrations well below those required to activate Ca2+ release. The mechanism and physiological significance of this most unusual desensitisation phenomenon are unclear. More recently, NAADP has been shown to mobilise Ca2+ in ascidian oocytes, brain microsomes and pancreatic acinar cells suggesting a more widespread role in Ca2+ signalling. A possible role for this novel Ca2+ release mechanism in sea urchin egg fertilisation is discussed.